ANALISIS KRIMINOLOGI TINDAK PIDANA PENCABULAN TERHADAP ANAK DI WILAYAH HUKUM KEPOLISIAN RESOR BUKITTINGGI - FEBRINA, WILLIAN (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
Crimes of sexual abuse against children are regulated in Article 76 of Law Number35 of 2014 concerning Child Protection. Child abuse is one of the social problems that arevery disturbing to the community so that it needs to be prevented and overcome. Thecriminal act of sexual abuse that occurred in the jurisdiction of Polres Bukittinggi for thelast 3 (three years) has increased, so it is interesting to study from the criminology aspectby looking for the causal factors, so that efforts can be sought or solutions to overcomethem. The rise of sexual abuse that occurs can be caused by weak self-control and a weakpsychological condition of a person, but also because of technological factors such aswatching pornographic films that make the perpetrators unable to resist themselves andeconomic factors and factors of low education.